The soulmate equation - Lauren, Christina (Gallery Books, 2021)
"For readers of The Rosie Project and One Plus One, an "entertaining and moving" novel about what happens when a matchmaking company finds an ideal match in an unlikely pair, by the author of The Unhoneymooners"--